Pengaruh Variasi Jari-Jari Kolam Olak Tipe Trajectory Bucket terhadap Loncatan Hidrolis dan Peredaman Energi pada Spillway Tipe Ogee - Prasetyo, Yogik Hardian; , Jaji Abdurrosyid, ST., MT; , Gurawan Djati Wibowo, ST., M.Eng (2016)
The need for water is not always matched by the availability of water, both in space and time. One man's attempt to take advantage of the water so it can be streamed on the places that need water (irrigation water) is the making of the dam (weir). In the structure of the dam, a building that used to bestow the flood discharge excess goes into the reservoir is spillway. Before crossing the spillway water flow is subcritical water. While the flow after passing through the spillway transformed into super-critical flow. So that energy with the grinding force that arise within the flow must be reduced to achieve a normal level of return. To reduce the energy contained in the flow, then at the downstream end of the launcher channel are ussually made energy absorbers buildings or stilling basin. The radius of stilling basin very influential in reducing energy, so radius of stilling basin should be planned at an appropriate curvature to produce energy reduce effective and efficient. The purpose of this study to determine the effect of various stilling basin radius for water velocity, turbulence and energy reduction. The experiments in this study conducted at the laboratory of hydraulics Department of Civil Engineering Faculty of Engneering, University of Muhammadiyah Surakarta. This experiment using a flume with a size of 30 cm x 60 cm x 1000 cm with a slope of 0,0058 channel basis. Using top point of weir ogee type and stilling basin trajectory bucket type and use five fingers variations stilling basin. The experiments was conducted with the 5 series, each of the six variations of discharge, so that the total running done as many as 30 running. At each discharge is done test of water long jump, high jump water and energy loss. The result of experiment show some conclusions. First, the radius stilling basin 8 cm trajectory bucket type is the most effective to reduce the energy flow which applies to all discharge. Second, the radius stilling basin 8 cm is the most effective to reduce of turbulence flow in downstream vortex. Third, the best radius stilling basin to reduce long jump water is 6,5 cm which has average length of the water jump lowest is 18,667 cm. Because of the shorter leap of water then the better the energy reduction. Fourth, Froude number in this experiment is directly proportional to the lenght of a water jump. This applies to all radius stilling basin except 7,5 cm radius due to the radius of flow separation occurred. Keywords : weir, spillway ogee, trajectory bucket, radius of stilling basin, velocity water, turbulence, energy reduced.